A comparative study on the institutional determinants of social entrepreneurial activity: The moderating effect of capitalism - Sabine Nadarević; Alexander Martin (Dr. Werner Jackstädt-Zentrum für Unternehmertum und Mittelstand, 2020)
Social entrepreneurship intrigues researchers as well as practitioners because of its unique character: Social entrepreneurs apply business strategies to achieve a social mission and add value to society. As a young field of research, social entrepreneurship is still dominated by conceptual work and qualitative studies. By using the data of the Global Entrepreneurship Monitor (GEM 2009) and additional data sources, this study applies a comparative research design and investigates the determinants of social entrepreneurial activity. Following recent calls, it focuses on the impact of capitalism on social entrepreneurial activity on the national level. The objective of this study therefore is to investigate whether cross-country variations in social entrepreneurial activity can be explained by incorporating the type of capitalism. Drawing on institutional theory and on ideas derived from the debate on the varieties of capitalism, the joint impact of gender equality, post-materialism (both supply factors) and capitalism (demand factor) is investigated. Performing hierarchical multiple regressions (n=39), our results show that all factors contribute to explaining cross-country variations in social entrepreneurial activity, but they do so in different ways. In line with research, our study supports the finding that post-materialism unfolds the greatest impact on social entrepreneurial activity. The impact of gender equality is less clear and, overall, weaker. Capitalism itself, however, has no direct impact on social entrepreneurial activity. Instead, this factor seems to leverage the effect of post-materialism on social entrepreneurial activity. Based on these findings, we conclude that demand factors (such as capitalism) seem to play an important role in facilitating the impact of supply factors (such as post-materialism). It appears that demand factors do not work independently from supply factors, while the opposite seems to be valid. We further conclude that it is insufficient to have given demands for social entrepreneurial activity. Rather, demand for social entrepreneurial activity must be acknowledged, recognized, and valued as an opportunity for social entrepreneurship.
Keywords: 650